Kompetensi Kepribadian Guru PAK dalam Menerapkan Norma Religius untuk Membentuk Karakter Siswa SMA Idanogawo - Yatinia Waruwu (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The personality competence of Christian Religious Education (PAK) teachers is very important in creating a learning environment that supports the development of student character, especially through the application of religious norms that are in line with Christian teachings. This study aims to analyze the personality competence of Christian Religious Education (PAK) teachers in applying religious norms for the formation of student character at SMA Negeri 1 Idanogawo, Nias Regency. This study uses a qualitative library approach through book and journal theories. The results of the study indicate that competence opens up new opportunities to enable teachers to integrate religious norms into the learning process for students. This role is also taught to students through Bible stories, discussions, and daily behavior. This paper concludes that the personality of Christian Religious Education (PAK) teachers not only enriches teaching materials, but also plays an important role in forming student character, which is in line with religious values ​​so that through the practice of religious norms as an example it greatly supports the formation of better student character.